The Iraqi state and Gaps of Its Building Process (قضايا سياسية, 2023)
By the process of state building, we mean that process that begins with strengthening the authority of the state and increasing its responsive ability, and it comes as a result of the weakness that some countries suffer from in the ability to achieve the goals for which they were found, which may threaten their continuity, so the gaps in the state building process focus in those gaps that constituted obstacles to strengthening the state's authority and its responsive ability. With regard to the Iraqi case, we believe in the importance of two variables that have had and still have a significant impact on creating practical gaps in the process of Iraqi state building, namely the weakness of political authority and cultural diversity.The impact of the variable of divided society was reflected in the Iraqi state building process through the identity crisis that appears, as Professor (Lucian Bay) believes, when the physical and psychological challenges are inappropriate and unacceptable in light of the new historical conditions.the issue of (Iraq's identity) and (Who is the Iraqi and to whom does he belong?) represents a fundamental focal point in the process of Iraqi state building, which lacks intellectual, sectarian, and religious unity, so it is scattered forces and divided society. This requires building a strong army, strengthening political institutions, and then recognizing divided society.Finally, it can be said that recognizing the rights of societal components with the weakness of political power is not commensurate with the state-building process unless the chronology is observed in the state-building process.